NCMP-07. CASE SERIES OF REGULARLY SCHEDULED MANNITOL INFUSIONS SHOWING WITH PROLONGED CLINICAL BENEFIT FOR MANAGEMENT OF CEREBRAL EDEMA IN GLIOMAS. (14th November 2022) - Chow, Jared; Carrillo, Jose; Kesari, Santosh; Sharma, Akanksha; Nguyen, Minh; Truong, Judy; Wagle, Naveed
Abstract: Gliomas account for the vast majority of malignant primary tumors arising in the central nervous system. Elevated intracranial pressure (ICP) may be a potentially devastating complication of brain tumors and hydrocephalus. Brain tumors may occupy significant space causing displacement and compression of delicate structures within a finite intracranial compartment. The compliance relationship is nonlinear and decreases as the combined volume of the intracranial contents increases. When these compensatory mechanisms have been exhausted, significant increases in pressure develop with relatively small increases in volume. The diagnosis of elevated ICP is generally based on clinical findings and corroborated by imaging studies and the patient's medical history. The best therapy for intracranial hypertension (ICH) is the resolution of the proximate cause of elevated ICP such as the evacuation of a blood clot, resection of a tumor, or cerebrospinal fluid (CSF) diversion in the setting of hydrocephalus. If these modalities have been exhausted or unavailable, osmotic diuretics such as mannitol can be utilized. This medication reduces brain volume by drawing free water out of the tissue and into the circulation, where it is excreted by the kidneys, thus dehydrating brain parenchyma. The common belief is that effects are usually present within minutes, peak at approximately one hour, and last 4 to 24 hours. We report a series of 33 patients treated for a minimum of 1 month of regularly scheduled maintenance infusions of Mannitol 1g/kg every two weeks, 64% showed improved clinical outcomes or stabilization of edema clinical symptoms. Patients expressed improvements in headaches, dizziness, and cognitive ability. This supports the bi-weekly maintenance use of Mannitol in glioma patients with symptomatic cerebral edema. A controlled trial should be supported. This series also suggest a mechanism of action with a more durable response than osmotic diuresis.